Pengaruh Penerapan Pendekatan Saintifik Terhadap Hasil Belajar Sains Siswa Kelas V SD Inpres Paccinongan Kabupaten Gowa - Khaerun Nisa’a Tayibu; Rahmah Kumullah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This type of research is survey research with quasi-experimental technique. The research population is all V SD Inpres Paccinonga, Gowa Regency in the 2015/2016 academic year. The population is 60 people who are divided into two classes, namely class IV A and class IV B with the sampling technique is total sampling. The results of this study indicate that the learning outcomes of fifth grade students of SD Inpres Paccinongan, Gowa Regency using an approach are 66.33 and conventional techniques are 57.10 in the range of values 10-100. In addition, the data on the results of the effectiveness analysis in the t test, shows the empirical value (tt): 7.16 while the theoretical value (ta): 1.67 at the 95% significance level, so it is stated that the empirical t value is greater than the theoretical t value. (table) (7.16>1.67) which means that the scientific approach is effective in improving science learning outcomes for fifth grade students of SD Inpres Paccinongan, Gowa Regency.